Study of Workers' Cattle Business Income (Case Study: Alindau District, Donggala Regency, Central Sulawesi Province) - Suharno, Suharno; Lahandu, Jamlis (FAPETKAN UNTAD, 2019)
The study aims to determine the costs and business income of cattle workers in households in Alindau Village, Sindue Tobata District, Donggala Regency. The study was conducted in Alindau Village, Sindue Tobata District, Donggala Regency for one month (January 24 to February 26, 2016). Research data were collected through observation and interviews, with 17 respondents. Data were analyzed using descriptive statistical analysis. Based on the results and discussion, it can be concluded that the total production costs incurred by working cattle breeders in Alindau Village, Sindue Tobata District, Donggala Regency amounted to Rp 5,897,352.94 / year with revenues of Rp. 27,261,176 / year so that an income of Rp 21,363,824 / year is obtained.